2015
DOI: 10.1210/me.2014-1201
|View full text |Cite
|
Sign up to set email alerts
|

Role of Sphingosine Kinase/S1P Axis in ECM Remodeling of Cardiac Cells Elicited by Relaxin

Abstract: The initiation and progression of heart failure is linked to adverse cardiac remodeling of the extracellular matrix (ECM) during disease mainly through the deregulation of myocardial metalloproteinases (MMPs). Relaxin (RLX), a peptide hormone acting as a physiological cardiac effector, is a key regulator of ECM remodeling in reproductive and nonreproductive tissues. Studying primary cultures of mouse cardiac muscle cells and rat H9c2 cardiomyoblasts, we have obtained evidence for a new signaling pathway activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 63 publications
1
35
0
Order By: Relevance
“…The role of S1P in TGF-β-induced fibrogenic effect in cardiac fibroblasts is further supported by a study showing that apelin, an adipocyte-derived cardioprotective factor, prevents TGF-β-stimulated activation of cardiac fibroblasts and collagen accumulation through inhibiting SPHK1 (85). Another study demonstrates that relaxin, a peptide hormone that stimulates the turnover of ECM, increases S1P formation, whereas inhibition of SPHK prevents the effects of relaxin on ECM remodeling and cell differentiation in cultured mouse cardiac muscle cells and rat cardiomyoblasts, suggesting that S1P signaling may participate in the ECM remodeling (86). S1P is also shown to stimulate cardiac fibroblast proliferation and migration via S1P3 receptor in vitro (87).…”
Section: S1p Signaling In Heartmentioning
confidence: 99%
“…The role of S1P in TGF-β-induced fibrogenic effect in cardiac fibroblasts is further supported by a study showing that apelin, an adipocyte-derived cardioprotective factor, prevents TGF-β-stimulated activation of cardiac fibroblasts and collagen accumulation through inhibiting SPHK1 (85). Another study demonstrates that relaxin, a peptide hormone that stimulates the turnover of ECM, increases S1P formation, whereas inhibition of SPHK prevents the effects of relaxin on ECM remodeling and cell differentiation in cultured mouse cardiac muscle cells and rat cardiomyoblasts, suggesting that S1P signaling may participate in the ECM remodeling (86). S1P is also shown to stimulate cardiac fibroblast proliferation and migration via S1P3 receptor in vitro (87).…”
Section: S1p Signaling In Heartmentioning
confidence: 99%
“…Along this line, much attention has been given in the recent years to molecules with anti-fibrotic effects [13][14][15]. In this context, studies conducted by our group and others have shown that the hormone relaxin can contribute to counteract fibrosis, inhibiting myofibroblast differentiation and modulating the expression of MMPs [16][17][18][19]. Moreover, emerging evidence suggests that cell-based therapy, utilizing mesenchymal stromal cells and other cell types, could attenuate the fibrogenic response in different tissues [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The naturally occurring hormone, relaxin, has emerged as an effective anti-fibrotic in several organs (reviewed in Samuel and Hewitson, 2006 ; Bennett, 2009 ; Du et al, 2014 ) including the aged ( Samuel et al, 2004b ; Danielson et al, 2006 ) and injured ( Garber et al, 2001 , 2003 ; McDonald et al, 2003 ; Lekgabe et al, 2005 ; Hewitson et al, 2010 ; Sasser et al, 2011 ; Yoshida et al, 2012 , 2013 ) kidney. Relaxin has been well-demonstrated to inhibit TGF-β1-induced myofibroblast differentiation and myofibroblast-induced aberrant ECM/collagen production ( Unemori and Amento, 1990 ; Unemori et al, 1996 ; Samuel et al, 2004a ; Heeg et al, 2005 ; Mookerjee et al, 2009 ), while also being able to augment ECM/collagen degradation through its ability to up-regulate various collagenases ( Unemori et al, 1996 ; Bennett et al, 2003 ; Kapila et al, 2009 ; Samuel et al, 2011 ; Ahmad et al, 2012 ; Chow et al, 2012 ; Bennett et al, 2014 ) and gelatinases ( Lekgabe et al, 2005 ; Kapila et al, 2009 ; Conrad and Shroff, 2011 ; Ahmad et al, 2012 ; Chow et al, 2012 ; Sassoli et al, 2013 ; Frati et al, 2015 ; Sarwar et al, 2015 ) and/or inhibit TIMP activity ( Unemori and Amento, 1990 ; Williams et al, 2001 ; Samuel et al, 2008 ; Sassoli et al, 2013 ; Bennett et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%